Cutaneous nodular fasciitis in the dog. Morphological and immunohistochemical study - Conceição , Lissandro G.; Acha , Livia M. R.; Moreira , Jose C. L.; Loures , Fabricia H.; Silveira, Lucia M. R.; Amorim, Renee L.; Neto, Rafael T. (Brazilian Journal of Veterinary Pathology, 2009)
Nodular fasciitis is a benign soft tissue lesion commonly diagnosed in human beings, but with rare description in dogs and cats. A female, spayed, 7.5 years old, otherwise healthy Labrador was examined because of a nodular growth of rapid development in the infraorbital region. The histopathological examination from the excisional biopsy revealed a well circumscribed proliferation of plump and moderately pleomorphic fibroblasts and vascular proliferation with a small central area of degeneration. Nodular fasciitis was diagnosed and several months pos surgical excision, no recurrence was observed. This report illustrates an histologically well circumscribed lesion of cutaneous nodular fasciitis in a dog, similar to some lesions in human beings and different from what is usually reported in veterinary patients.